ANALISIS PRAGMATIS ~NO DA DALAM TUTURAN - Wiyatasari, Reny (IZUMI, 2017)
~Nda form that appear at the end of the Japanese sentence serves as the modalities of explanation and conjecture. This modalities often used in conversations. Therefore it may be expressed this modality has a significant role in building a Japanese sentence structure. This study focused on the use of the modality ~ noda through speech tangible examples of data taken from the drama series Kareni yoroshiku Sono toki (2007). From the data source will get a variety of shapes ~ nodesu, as well known in the utterances with what illocutionary ~  nodesu used, and how the role of ~ nodesu in the utterance. In order to get the results of the analysis in accordance with the problem, then the data were analyzed using mean semantics or pragmatics with contextual analysis method and the padan analysis method. Based on the analysis, it is known modality ~ noda possible to be able to appear and be used in utterances that contain illocutionary meaning: to say to the form ~ nda, apologized to the shape of ~ ndesukedo, inquire with the form ~ ndesuka, blaming the form ~ ndayo, thanks to ~ ndesune form, stating the form ~ ndatte, assured by the shape datte ~ ndayo.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor